Trends in adult chlamydia and gonorrhoea prevalence, incidence and urethral discharge case reporting in Mongolia from 1995 to 2016 – estimates using the Spectrum-STI model - Jugderjav Badrakh; Setsen Zayasaikhan; Davaalkham Jagdagsuren; Erdenetungalag Enkhbat; Narantuya Jadambaa; Sergelen Munkhbaatar; Melanie Taylor; Jane Rowley; Guy Mahiané; Eline Korenromp (Western Pacific Surveillance and Response, 2017)
Objective: To estimate Mongolia’s prevalence and incidence trends of gonorrhoea and chlamydia in women and men 15–49 years old to inform control of STIs and HIV, a national health sector priority. Methods: We applied the Spectrum-STI estimation model, fitting data from two national population surveys (2001 and 2008) and from routine gonorrhoea screening of pregnant women in antenatal care (1997 to 2016) adjusted for diagnostic test performance, male/female differences and missing high-risk populations. Prevalence and incidence estimates were then used to assess completeness of national case reporting. Results: Gonorrhoea prevalence was estimated at 3.3% (95% confidence interval, 1.6–3.9%) in women and 2.9% (1.6–4.1%) in men in 2016; chlamydia prevalence levels were 19.5% (17.3–21.9%) and 15.6% (10.0–21.2%), respectively. Corresponding new incident cases in women and men in 2016 totalled 60 334 (36 147 to 121 933) and 76 893 (35 639 to 254 913) for gonorrhoea and 131 306 (84 232 to 254 316) and 148 162 (71 885 to 462 588) for chlamydia. Gonorrhoea and chlamydia prevalence declined by an estimated 33% and 11%, respectively from 2001 to 2016. Comparing numbers of symptomatic and treated cases estimated by Spectrum with gonorrhoea case reports suggests that 15% of symptomatic treated gonorrhoea cases were reported in 2016; only a minority of chlamydia episodes were reported as male urethral discharge cases. Discussion: Gonorrhoea and chlamydia prevalence are estimated to have declined in Mongolia during the early 2000s, possibly associated with syndromic management in primary care facilities and improving treatment coverage since 2001 and scale up of HIV/STI prevention interventions since 2003. However, prevalence remains high with most gonorrhoea and chlamydia cases not treated or recorded in the public health system.